Fatigue Behaviour of Basalt and Glass Fiber Reinforced Polymer Composite Filled with Granite Fly Ash - Jaafar, Mohd Azrul; Abdullah, Shahrul Azam; Jumahat, Aidah; Mohd Zahib, Zaidahtulakmal; Raja Ahsan Shah, Raja Mazuir; Muslim, Mohamad Asrofi; Raymond Siew Teng Loy (International Journal of Integrated Engineering, 2025)
The granite processing industry produces substantial amounts of residual granite waste daily. This waste is collected through a filtration process during the drying and heating stages of concrete mixture production. This study conducts an experimental investigation into the potential use of granite fly ash (GD) as a filler to enhance the fatigue properties of basalt/glass composites (BFRC/GFRC). The research focuses on evaluating the tensile and fatigue characteristics of the developed fiber-reinforced polymer (FRP) composites. Composite samples were fabricated by incorporating granite fly ash (GD) in varying proportions, namely 1wt%, 3wt%, and 5wt%. The FRP laminates were produced using a hand lay-up technique with silicon mold and were cut using a cutting machine. The study’s findings indicate significant improvements in tensile and fatigue properties, especially for FRP with 3% weight loading, in both BFRC and GFRC. Notably, adding just 1wt% granite fly ash (GD) resulted in an 8.6% increase in tensile and a substantial 26.9% increase in modulus for the BFRC composite. Under fatigue loading, the fatigue properties of the BFRP specimens showed better fatigue properties compared to GFRC. Furthermore, enhanced fatigue life counts were noted for the composite labeled BG3, which includes 3.0 vol% granite fly ash. However, an increase to 5.0 vol% resulted in a reduction in fatigue life counts. In summary, the study highlights the beneficial impact of incorporating granite fly ash, particularly within the 1%, 3%, and 5% weight range, on the mechanical properties of both BFRC and GFRC composites.